Repeated Lineage Switches in an Elderly Case of Refractory B-Cell Acute Lymphoblastic Leukemia With MLL Gene Amplification: A Case Report and Literature Review - Takeda, Reina; Yokoyama, Kazuaki; Fukuyama, Tomofusa; Kawamata, Toyotaka; Ito, Mika; Yusa, Nozomi; Kasajima, Rika; Shimizu, Eigo; Ohno, Nobuhiro; Uchimaru, Kaoru; Yamaguchi, Rui; Imoto, Seiya; et al. (Frontiers in Oncology, 2022)
Lineage switches in acute leukemia are rare, and the underlying mechanism is poorly understood. Here, we report the case of an elderly patient with leukemia in which the leukemia started as B-cell acute lymphoblastic leukemia (B-ALL) that changed to B- and T-cell mixed phenotype acute leukemia (MPAL) and then acute myeloid leukemia (AML) during consecutive induction chemotherapy treatments. A 65-year-old woman was initially diagnosed with Philadelphia chromosome-negative B-ALL, which primarily expressed TdT/CD34/HLA-DR; more than 20% of blasts were positive for CD19/CD20/cytoplasmic CD79a/cytoplasmic CD22/CD13/CD71.The blasts were negative for T-lineage markers and myeloperoxidase (MPO). Induction chemotherapy with the standard regimen for B-ALL resulted in primary induction failure. After the second induction chemotherapy regimen, the blasts were found to be B/T biphenotypic with additional expression of cytoplasmic CD3. A subsequent single course of clofarabine as the fourth induction chemotherapy regimen dramatically reduced the levels of lymphoid markers. However, myeloid markers, such as MPO, became positive, and the leukemia completely changed its lineage to AML. Despite subsequent intensive chemotherapy designed for AML, the leukemia was uncontrollable, and a new monoblastic population emerged. The patient died approximately 8 months after the initial diagnosis without experiencing stable remission. Several cytogenetic and genetic features were commonly identified in the initial diagnostic B-ALL and following AML, suggesting that this case should be classified as lineage switching leukemia rather than multiple cancers simultaneously developing as de novo B-ALL and de novo AML or as primary B-ALL and therapy-related myeloid neoplasm. A complex karyotype was persistently observed with hemi-allele loss of chromosome 17, where a tumor suppressor gene, TP53, is located. As the leukemia progressed, the karyotype became more complicated with the additional abnormalities. Sequential target sequencing revealed that the variant allele frequency of TP53 mutations gradually increased. In addition, fluorescent in situ hybridization (FISH) revealed an increased number of mixed-lineage leukemia (MLL) genes, both before and after lineage conversion. In contrast, FISH was negative for MLL rearrangements, which are well-known abnormalities associated with lineage switching leukemia and MPAL. To the best of our knowledge, this is the first case of acute leukemia with lineage ambiguity with MLL gene amplification.